Evaluating an Instructional Textbook: A Critical Discourse Perspective - ali roohani; najmeh heidari (Issues in Language Teaching, 2012)
A critical discourse analysis (CDA) of English language teaching (ELT) textbooks can provide a theoretical description of existing ideological effects in the texts and a means to link linguistic and social practices. This study, thus, seeks to evaluate Summit 2B (i.e., the advanced book of Top Notch series) with a focus on the representation of male and female social actors. In so doing, this study drew on van Leeuwen’s (1996) social actor framework and Halliday’s (2004) transitivity model. To achieve the purpose of this study, content analysis was first carried out in the corpora obtained from the aforementioned textbook to find out the frequency and proportion of various social actors. The results obtained from the tests of significance (i.e., chi-square tests) and the qualitative data analyses revealed that there were some significant differences between males and females concerning role allocation (i.e., activation, subjection, and beneficialization), substitution (personalization/impersonalizaton), and personal pronouns. Compared with females, males were represented as more active, energetic, independent, and assertive forces; males were represented more frequently and placed in high-status positions; they were also individualized more frequently. The results indicated that though females and males were almost equally informalized and indetermined, there was not much serious attempt to eliminate the gender bias in Summit, used as a substitute for other ELT textbooks used in private language institutes in Iran. The findings suggest that textbook writers and publishers should be more cautious about the gender discourse, along with other criteria making ELT textbooks work, because gender bias can affect language learners’ perception and preference for the choice of language in second or foreign (L2) communication.